Large nonlinear optical effect in tungsten bronze structures via Li/Na cross-substitutions. Issue 60 (23rd June 2020) - Chu, Shihang; Lin, Kun; Yang, Tao; Yu, Chengyi; Cao, Yili; Zhang, Yujuan; Sun, Yujiao; Li, Zerui; Jiang, Xingxing; Lin, Zheshuai; Li, Qiang; Chen, Jun; et al.
Abstract : By a simple cross-substitution of Li/Na in a tungsten bronze structures, the SHG response was significantly prompted to ∼47 × KDP, manifesting local distortion be a possibly general route to improve NLO effect in stiff and low symmetric structures. Abstract : By a simple cross-substitution of A-site Li/Na in tetragonal tungsten bronze (TTB) structures, we successfully synthesized a new niobate compound, Pb2.15 (Li0.25 Na0.75 )0.7 Nb5 O15, with a superstructure. This compound exhibits a strong second harmonic generation (SHG) up to ∼47 × KDP. The large SHG response is related to strengthened local distortion, manifesting cross-substitution as a possibly general route to improve the NLO effect in stiff and low symmetric structures.